Adiabatic sheath model for beam-driven blowout plasma channels - Yulong Liu; Ming Zeng; Lars Reichwein; Alexander Pukhov (Physical Review Research)
In plasma wakefield accelerators, the structure of the blowout sheath is vital for the blowout radius and the electromagnetic field distribution inside the blowout. Most previous theories assume artificial distribution functions for the sheath, which are either inaccurate or require prior knowledge of parameters. In this paper, we use an adiabatic sheath model based on force balancing to overcome these limitations. This model gives self-consistent forms of the sheath and pseudopotential distribution and estimates the balancing radius of the blowout channel better than previous models. Our findings not only enhance the understanding of sheath dynamics but also offer a self-consistent theoretical foundation for future studies on nonlinear phenomena in the blowout channel.